Kombinasi Model Trip Generation-Modal Split (G-MS) Dalam Perencanaan Bus Bandara Terintegrasi - Hasahatan Dalimunte, Irham; Buchari, Erika; Herno Della, Rhaptyalyani (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2024)
The modal split model can be varied to other model in the concept of four step models transportation. This approach model can be varied depending on the purpose of transport planning, such as the modal split planning process which is carried out at the trip generation calculation stage, and in this process the movement of public transport can be directly separated from private transport with the assumption that someone who will travel can choose the model that is influenced by socioeconomic valiable. The model combined experiment (G-MS) was carried out on the route to and from Jambi’s Sultan Thaha Airport, which is one of the transportation nodes that plays an important role in regional development in Jambi City. The aim of this research is to analyze potential demand using a combination of the Trip Generation-Modal Split (G-MS) model. Based on the results of the analysis using the binomial ratio logit model with the value Y = Proportion of passengers/days. The passenger distribution area is devided base on zones where the zones that have the potential to be passenger gathering point are zone 9, zone 10 and zone 11. Calculation of the chi-square test (goodness of fit test) shows that the calculation X2 value is 11.583 and the table X2 is 14.067 because X2 count <X2 table, then H0 is accepted which means the observation results are the same as the average model results so that model validation is declared successful, so this research can be used to calculate passenger demand to plan airport buses.